VD_FINDINFO HC / 2015 / 95 vom 22. Dezember 2014 - VD Tribunal cantonal (2014)
PARTAGE SUCCESSORAL, ACTION EN PARTAGE SUCCESSORAL, PACTE SUCCESSORAL, CHOSE SANS MAÎTRE | 494 CC, 573 al. 2 CC, 626 CC, 230a LP